Biology and treatment of BRAF mutant metastatic melanoma. (March 2016) - Kong, Benjamin Y; Carlino, Matteo S; Menzies, Alexander M
BRAF inhibitors were among the first systemic therapies to show clinical benefit in metastatic melanoma. Here, we review the spectrum of BRAF mutations in melanoma, their role in oncogenesis, clinicopathological associations and response to treatment. The differing biology and clinical features of V600E- and V600K-mutated melanoma are outlined. The molecular changes associated with BRAF fusion genes and their response to targeted therapies, as well as the role of immunotherapy in treatment sequencing with targeted therapies are discussed.